2014
DOI: 10.1002/marc.201400238
|View full text |Cite
|
Sign up to set email alerts
|

Complex Macrophase‐Separated Nanostructure Induced by Microphase Separation in Binary Blends of Lamellar Diblock Copolymer Thin Films

Abstract: The nanostructures of thin films spin-coated from binary blends of compositionally symmetric polystyrene-b-polybutadiene (PS-b-PB) diblock copolymer having different molar masses are investigated by means of atomic force microscopy (AFM) and grazing-incidence small-angle X-ray scattering (GISAXS) after spin-coating and after subsequent solvent vapor annealing (SVA). In thin films of the pure diblock copolymers having high or low molar mass, the lamellae are perpendicular or parallel to the substrate, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Vertical vs Lateral Macrophase Separation: Effect of the Film Thickness. Several experimental investigations have demonstrated that macrophase separation in mixed copolymer films can occur along the vertical axis, i.e., along the film normal, 35 or within the film plane, i.e., laterally. 37 Figure 3 illustrates these types of phase separation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vertical vs Lateral Macrophase Separation: Effect of the Film Thickness. Several experimental investigations have demonstrated that macrophase separation in mixed copolymer films can occur along the vertical axis, i.e., along the film normal, 35 or within the film plane, i.e., laterally. 37 Figure 3 illustrates these types of phase separation.…”
Section: Resultsmentioning
confidence: 99%
“…36 We focus here on the simplest mixture, where both diblock copolymers are compositionally symmetric, and contain only two types of monomers, A and B. Under confinement, phase separation in such a system may occur in the vertical (normal) direction to the substrate, 35,38 or in the film plane, 37 i.e., in the lateral direction. Zhang et al 35 experimentally observed vertical phase separation in mixtures of two compositionally symmetric polystyrene-b-polybutadiene diblock copolymers with a ratio of short-to-long copolymer lengths of 0.13 at a moderate film thickness of 2.3 times the period of the pure thick lamellae.…”
Section: Introductionmentioning
confidence: 99%
“…the drying rate [121,[136][137][138][139][140], particularly at vapor pressure maxima well below saturation. The most advanced set-ups use mass-flow controllers [141].…”
Section: In-situ Sample Environments For Svamentioning
confidence: 99%
“…The chamber described in Ref. [141] is shown schematically in Figure 7a. Several versions of this type of chamber were developed by us.…”
Section: Chambers Based On a Flow Of Solvent Vapormentioning
confidence: 99%
“…Compared to SAXS mode, the X-ray beam in GISAXS mode hits the sample with a very small incident angle (usually smaller than 1 ), exploiting the finite penetration depth of totally reflected X-rays into the material; this geometry is extremely surface sensitive and allows us to investigate thin films down to the nanometre scale in thickness (Mü ller- Buschbaum et al, 1999Buschbaum et al, , 2000. Because high brilliance and collimation of the X-ray beam are required, most in situ GISAXS experiments are performed at synchrotron radiation facilities, such as SSRF, BSRF and DESY (Roth et al, 2007;Papadakis et al, 2008;Di et al, 2010;Cheng et al, 2011;You et al, 2011;Zhong et al, 2011Zhong et al, , 2013Zhang et al, 2013Zhang et al, , 2014aZhang et al, , 2014bZhao et al, 2014). Much work on modified synchrotron GISAXS facilities has been reported (Roth et al, 2006;Jerkily et al, 2013;Ogawa et al, 2013;Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%